Follow-Up of a Case of Dopamine-Mediated Yawning-Fatigue-Syndrome Responsive to Opioids, Successful Desensitization via Graded Activity Treatment - Payam Dibaj; Dagmar Seeger; Jutta Gärtner; Frank Petzke (MDPI AG, 2021)
A 60-year-old man suffering from recurrent attacks of yawning-fatigue-syndrome, triggered by mild exercise of his right leg since a temporary lumbar disc herniation 9 years ago, was initially treated with the oral µ-opioid-receptor agonist tilidine before each bout of exercise (see Dibaj et al. 2019 JAMA Neurology 2019;77:254). During the first few months, this treatment continuously prolonged the time without exercise-triggered yawning and fatigue. In the next few months of treatment, exercise was increased in a graded manner to alleviate the yawning-fatigue-syndrome. The number of repetitions of the physical exercises was gradually increased without taking the opioid beforehand. After several months, almost the same effort level without medication could be achieved by graded activity as before under the influence of opioid medication. Graded physical activity can thus disrupt complex pathophysiological mechanisms leading to yawning and fatigue.